Plasma sRAGE is independently associated with increased mortality in ARDS: a meta-analysis of individual patient data - Jabaudon, Matthieu; Lichtenstern, Christoph; Uhle, Florian (Intensive care medicine, 2018)
The soluble receptor for advanced glycation end-products (sRAGE) is a marker of lung epithelial injury and alveolar fluid clearance (AFC), with promising values for assessing prognosis and lung injury severity in acute respiratory distress syndrome (ARDS). Because AFC is impaired in most patients with ARDS and is associated with higher mortality, we hypothesized that baseline plasma sRAGE would predict mortality, independently of two key mediators of ventilator-induced lung injury.